Manajemen Rekrutmen Guru PAI di SMK Nurul Iman Palembang (Analisis Terhadap Proses dan Materi Seleksi) - Sari, Via Anjela; Zainuri, Ahmad; Kanada, Rabial; Ibrahim, Ibrahim (Sekolah Tinggi Agam Islam Sumatera Medan, 2021)
This study aims to analyze the management of teacher recruitment which focuses on the study process and selection material. This research was conducted at SMK Nurul Iman Palembang, as a school known for its quality in the recruitment and development of teachers. This study uses a qualitative method based on descriptive studies, with data collection techniques using observation, interviews, and documentation. Informants in this study were principals, vice principals, and teachers. The data analysis technique used is data reduction, data presentation and verification or drawing conclusions. The results of the study explain that the teacher recruitment process at SMK Nurul Iman Palembang goes through the stages of preparation for teacher recruitment, formation of a teacher recruitment committee, dissemination of recruitment information, acceptance and collection of administration, preparation of selection materials, interviews, and determination of participant graduation. The selection materials include four materials as stated in Law no. 14 of 2005 concerning teachers and lecturers, namely pedagogical material, professional material, personality material, and social material.